Tension-Band Ankle Arthrodesis: An Update. Issue 2 (June 2016) - Sagherian, Bernard H.; Patterson, Jason A.; Chivers, F. Spencer; Kile, Todd A.; Barker, Lloyd G.; Probst, Nicholas E.; Claridge, Richard J.
Abstract : Ankle arthrodesis remains the gold standard for the treatment of end-stage ankle arthritis, despite the significant improvement in the clinical outcomes of total ankle arthroplasty because of newer designs. Posttraumatic degeneration is the most common cause of ankle arthritis. Other causes include infection, systemic arthritides, and avascular necrosis. Many tibiotalar arthrodesis techniques have been described with varying fusion and complication rates. This paper describes a reliable and reproducible technique of ankle arthrodesis based on the tension-band technique and modern internal fixation principles. This technique results in very high fusion rates with few complications. Level of Evidence: Diagnostic Level 4. See Instructions for Authors for a complete description of levels of evidence.